D1S-Neuro Program: Frequency and Risk Factors for the Development of Diabetic Neuropathy in Pediatric Patients with Type 1 Diabetes Mellitus, a Single Center Study - Marco Piccoli; Joaquin Gutierrez de Rubalcava Doblas; Patrizia Furlan; Silvia Cocchio; Alessandro Zamberlan; Gloria Panzeri; Vincenzo Baldo; Carlo Moretti (Biomedicines)
Introduction: Diabetic neuropathy is the most common long-term complication of diabetes mellitus, widely studied in the adult population, but its prevalence in children and adolescents has not yet been clearly defined. Materials and Methods: Diabetic patients over 11 years old and with at least 5 years of diabetes were subjected to specific tests for the screening of diabetic peripheral neuropathy (DPN) and for the diagnosis of cardiac autonomic neuropathy (CAN). Additionally, all data related to the patients’ average hemoglobin (HbA1c) levels over the last year and the past 5 years and the monitoring and insulin delivery technology used were collected. Results: Tests were performed on a total of 81 patients. DN diagnostic tests identified 17 patients with signs of neuropathy (21.0%), specifically 11 with DPN (13.6%) and 7 with CAN (8.6%). Data showed that the 5-year HbA1c of those diagnosed with DPN was significantly higher compared to those without a diagnosis. The analysis also highlighted that an average HbA1c level over 5 years greater than 8.5% increases the risk of DPN by 10 times. Conclusions: This article confirms that diabetic neuropathy begins to develop even in pediatric patients, that various nerve conduction systems may be affected, and that poorer glycometabolic control is associated with an increased risk of developing DN. These results highlight the importance of early screening and prevention through tight glycometabolic control.